Development of a Stunting Prevention Model in Pre-Prosperous Families: Delphy Study - Sudirman, Jumrah; Lestari, Ayu; Thamrin, Halida; Syafar, Muhammad (Jurnal Bidan Cerdas, 2024)
Introduction:Stunting conditions are very close to family welfare conditions, so one way to reduce the prevalence of stunting is to involve the role of the family. Purpose:This study aimed to develop a stunting prevention model in underprivileged families with expert consensus. Methods: The method used in this research is a Delphi study which consists of 3 rounds. The Delphi Study Types used are classic Delphi and online Delphi. This research involved nine experts until the third round. The implementation of the Online Delphi round is sent via the WhatsApp application. Results: In the results obtained in the third round for Factors Affecting Stunting in underprivileged families, there are 11 sub-themes. For the efforts that need to be made to prevent stunting, especially for underprivileged families, there are 12 sub-themes and educational materials that need to be provided to prevent stunting, especially for underprivileged families there are nine sub-themes. Conclusion: Component analysis for developing a stunting prevention model through the Delphi study resulted in experts agreeing to develop educational materials on this model.